1965
DOI: 10.2337/diab.14.11.696
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Hypoglycemic Activity of Insulin after Intestinal Administration to the Rabbit

Abstract: The effect of insulin on blood glucose in the rabbit after direct instillation in the small intestine has been investigated. Crystalline Insulin, (U.S.P. U-40), administered via catheters placed in the duodenum, jejunum and ileum did not cause hypoglycemia at doses up to 50 U./kg. Tolbutamide (100 mg./kg.) produced a hypoglycemic response after oral and intestinal administration. The lack of response to insulin is believed to be due to the destruction of insulin by proteolytic enzymes of the gastrointestinal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1968
1968
1988
1988

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Some investigators 1 -12 -13 failed, however, to demonstrate a hypoglycemic effect of gastrointestinal administration of insulin. Tocus et al 13 have suggested that the lack of agreement in the work related to the intestinal absorption of insulin could be due to the different operative technics employed, and to differences in pH, in bacterial flora and in enzyme activity inside the gastrointestinal tract. In preliminary experiments, when saline or borate buffer was infused directly to the exposed portions of the gastrointestinal tract or to the ligated intestinal loop, a marked increase in blood glucose was often observed in some rabbits.…”
Section: Discussionmentioning
confidence: 98%
“…Some investigators 1 -12 -13 failed, however, to demonstrate a hypoglycemic effect of gastrointestinal administration of insulin. Tocus et al 13 have suggested that the lack of agreement in the work related to the intestinal absorption of insulin could be due to the different operative technics employed, and to differences in pH, in bacterial flora and in enzyme activity inside the gastrointestinal tract. In preliminary experiments, when saline or borate buffer was infused directly to the exposed portions of the gastrointestinal tract or to the ligated intestinal loop, a marked increase in blood glucose was often observed in some rabbits.…”
Section: Discussionmentioning
confidence: 98%